(untitled) (Nueva Epoca, 2025)
In this work, we propose to take stock of the incorporation of personal rights in the Civil and Commercial Code of the Nation. It examines the context of their inclusion within the framework of the constitutionalization and conventionalization of private law, based on the strengthening of human dignity. It also reviews the reception these rights have had in national jurisprudence. Finally, it highlights the new challenges facing the law in this area.